Diet Induced Obesity Alters Intestinal Cytoplasmic Lipid Droplet Morphology and Proteome in the Postprandial Response to Dietary Fat - D’Aquila, Theresa; Zembroski, Alyssa S.; Buhman, Kimberly K. (Frontiers in Physiology, 2019)
Dietary fat absorption by the small intestine is an efficient, multistep process that regulates the uptake and delivery of essential nutrients and energy. Fatty acids taken up by enterocytes, the absorptive cells of the small intestine, are resynthesized into triacylglycerol (TAG) and either secreted in chylomicrons or temporarily stored in cytoplasmic lipid droplets (CLDs). Proteins that associate with CLDs are thought to regulate the dynamics of TAG storage and mobilization. It is currently unclear what effect diet induced obesity (DIO) has on the balance between dietary fat storage and secretion. Specifically, there is limited knowledge of how DIO affects the level and diversity of proteins that associate with CLDs and regulate CLD dynamics. In the current study, we characterize CLDs from lean and DIO mice through histological and proteomic analyses. We demonstrate that DIO mice have larger intestinal CLDs compared to lean mice in response to dietary fat. Additionally, we identified 375 proteins in the CLD fraction isolated from enterocytes of lean and DIO mice. We identified a subgroup of lipid related proteins that are either increased or unique to the DIO CLD proteome. These proteins are involved in steroid synthesis, TAG synthesis, and lipolysis. This analysis expands our knowledge of the effect of DIO on the process of dietary fat absorption in the small intestine (D’Aquila, 2016).